Impact de l’alignement stratégique et de la culture digitale sur la réussite de la transformation digitale au sein de l’organisation publique Marocaine - Ben Dahhane, Anouar (2023)
Digital transformation is currently a hot topic and a strategic issue for all public and private organizations, regardless of their size. Having entered the "digital era", organizations are facing unprecedented transformations that disrupt their operations and management systems. However, the concept is new and it is not yet clear what factors influence or boost digital transformation. While previous theoretical and empirical work has allowed us to identify the impacts on the success of Digital transformation of the strategic alignment between the digital technologies implemented and the strategy of the public or private organization. Also, we have revealed that the digital culture is the guarantee of strategic coherence and success of the organization's digital transformation.The aim of this research project is to study the extent to which digital technology deployment projects are strategically aligned with the organization's overall strategy, and the degree to which digital culture impacts digital transformation within the organization. We mobilized a quantitative method by means of a questionnaire. A total of 52 respondents from the central entities of the Caisse Nationale de Sécurité Sociale (CNSS) completed the questionnaire. These were managers and executives involved in digital transformation initiatives.The theoretical model was tested using structural equation modeling. Analysis of the data collected using SMART PLS V4 highlights the crucial role of the CNSS establishment's strategy in value creation and the success of digital transformation. The results also indicate that to fully seize the opportunities and potential of this transformation, it is essential to embed a digital-focused organizational culture. In fine, the two hypotheses mobilized at the outset of the positive impact of strategic alignment and digital culture on the success of digital transformation are validated.